DEVELOPMENT OF EDUCATIONAL COMICS BASED ON SCIENTIFIC APPROACH TO IMPROVE UNDERSTANDING OF THE CONCEPT OF THE DIGESTIVE SYSTEM IN GRADE VIII STUDENTS OF MTs DARUL HIKAM - Intan Miladia Solihah; Sugeng Kurniawan; Yurnalisma Dewi (Scientechno: Journal of Science and Technology, 2026)
This study aims to develop educational comics based on a scientific approach on digestive system materials, assess their feasibility, test their effectiveness in improving understanding of concepts, and describe the response of grade VIII MTs Darul Hikam students to their use in science learning. The method used is research and development with the ADDIE model which includes the analysis, design, development, implementation, and evaluation stages, with test subjects as many as 25 grade VIII students as well as instruments in the form of expert validation sheets, pre-test and post-test tests, and student response questionnaires. The results of the study showed that the developed media obtained a very feasible category based on the validation of 100% and 96% media experts, 88% of material experts, and 95% and 95% of teacher practicality, while its effectiveness was shown by an increase in the average score from 43.6 in the pre-test to 89.6 in the post-test with an N-gain of 0.80 in the high category. The novelty of this research lies in the systematic integration of scientific approaches into the narrative flow of educational comics that are adapted to the context of MTs students and digestive system materials. The implications of this study show that educational comics can be an alternative science learning media that is contextual, interesting, and supports active learning to strengthen students' understanding of concepts and help teachers implement student-centered learning according to the demands of the Independent Curriculum in the tsanawiyah madrasah environment more effectively and relevant to learning needs.